Oxygen, carbon and sulphur isotope studies in the Keban Pb-Zn deposits, eastern Turkey: An approach on the origin of hydrothermal fluids - Kalender, Leyla (Pergamon-Elsevier Science Ltd, 2011)
Pb-Zn deposits are widespread and common in various parts of the Taurus Belt. Most of the deposits are of pyrometasomatic and hydrothermal origin. The Keban Pb-Zn deposits are located along the intrusive contact between the Paleozoic - Lower Triassic Keban Metamorphic Formation and the syenite porphyry of the Upper Cretaceous Keban igneous rocks. Various studies have already been carried out; using fluid inclusion studies on fluorite, calcite and quartz on the pyrite-chalcopyrite bearing Keban ore deposits. This study focuses on the interpretation of stable isotope compositions in connexion with fluid inclusion data. Sulphur isotope values (delta S-34) of pyrite are within the range of -0.59 to +0.17 parts per thousand(V-CDT) (n = 10). Thus, the source of sulphur is considered to be magmatic, as evidenced by associated igneous rocks and delta S-34 values around zero0. Oxygen isotope values delta O-18 of quartz vary between +10.5 and +19.9 parts per thousand((SMOW)). However, delta O-18 and delta C-13 values of calcite related to re-crystallized limestone (Keban Metamorphic Formation) reach up to +27.3 parts per thousand((SMOW)) and +1.6 parts per thousand(pDB), respectively. The delta S-34, delta C-13 and delta O-18 values demonstrate that skarn-type Pb-Zn deposits formed within syeno-monzonitic rocks and calc-schist contacts could have developed at low temperatures, by mixing metamorphic and meteoric waters in the final stages of magmatism. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Stable isotopes; Contact pyrometasomatic type; East Anatolian; Keban; Turkey